Fixed Point of Almost Contraction in b-Metric Spaces. (28th October 2020) - Iqbal, Maryam; Batool, Afshan; Ege, Ozgur; Sen, Manuel de la
Abstract : In this paper, we introduce a generalized multivalued (α, L )-almost contraction in the b -metric space. Furthermore, we prove the existence and uniqueness of the fixed point for a specific mapping. The result presented in this paper extends some of the earlier results in the existing literature. Moreover, some examples are given to illuminate the usability of the obtained results.